2013
DOI: 10.1097/sla.0b013e31828c4a19
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life After Gastrectomy for Adenocarcinoma

Abstract: Background Gastrectomy remains a major operation with potential for significant deterioration in patients’ health-related quality of life (QOL). This study assessed differences in QOL among patients following distal (DG), proximal (PG) or total (TG) gastrectomy. Methods We prospectively enrolled patients undergoing gastrectomy at our institution between 2002 and 2007. Participants completed the EORTC cancer (QLQ-C30) and gastric (QLQ-STO22) questionnaires preoperatively and at five postoperative intervals up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
108
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(118 citation statements)
references
References 18 publications
7
108
0
3
Order By: Relevance
“…In agreement with these previous studies, our results show that more than half of the patients experienced at least 10% of BWL after gastric cancer resection. In line with our results, previous studies have found a high prevalence of diarrhoea after gastric cancer resection ranging from 20% to 30% (6,7,10,11). In the present study, severe diarrhoea was more common in the group of patients with >10% BWL (13% versus 0%).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In agreement with these previous studies, our results show that more than half of the patients experienced at least 10% of BWL after gastric cancer resection. In line with our results, previous studies have found a high prevalence of diarrhoea after gastric cancer resection ranging from 20% to 30% (6,7,10,11). In the present study, severe diarrhoea was more common in the group of patients with >10% BWL (13% versus 0%).…”
Section: Discussionsupporting
confidence: 82%
“…A number of studies have described the great impact of gastric resection on HRQL in patients with curable gastric cancer (6,10). It has been shown that HRQL is influenced by the extent of resection (total vs. subtotal or proximal gastrectomy) (4,6) and there is a significant impairment of several aspects of HRQL reported by patients in the immediate postoperative period (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…What should be considered a specific problem for patients who undergo gastrectomy is that various postoperative symptoms that often lead to eating problems, malnutrition, and weight loss during the early postoperative period [8][9][10]. Besides, these consequences could eventually affect the prognosis of patients through decreasing their tolerance to evidence-based postoperative chemotherapy [11].…”
Section: Introductionmentioning
confidence: 99%